Modification of Alkaloid Structure in the Conium Drug with Fullerenes C60 - Zabolotnyi, M.A.; Momot, A.I.; Dovbeshko, G.I.; Gnatyuk, E.P.; Solyanyk, G.I.; Dmytrenko, O.P.; Kulish, N.P.; Fedina, K.V. (Ukrainian Journal of Physics, 2012)
The antineoplastic drug Conium, whose active components are piperidine alkaloids, and the possibility of a modification of its properties by fullerenes C60 are studied. The IR spectra of the mixture of the drug Conium and a fullerene water solution are obtained. The spectral manifestation of the formation of a complex of fullerene with one of the alkaloids, namely γ-coniceine, is detected. The existence of the complex and its spectral characteristics are confirmed by quantum-chemical computations with a Gaussian program. Moreover, the IR spectra are calculated, and the conformations of γ-coniceine are studied.